ANALISIS MODAL KERJA PT.TUNAS PRIMA SEJAHTERAH SAMARINDA - Tansil, Lisa (EKONOMIA, 2012)
Lisa Tansil , Working Capital Analysis PT . Tunas Prima Sejahterah samantha ( under the guidance of Mr. LCA . Robin Jonathan and Mrs. Elfreda A. Lau ) Management of working capital management regarding the company's current account ( current assets and current liabilities ) . Working capital management is one of the most important aspects of the overall management of corporate spending . If the company can not maintain " satisfactory level of working capital " , then it is likely the company in an insolvent ( unable to pay obligations already due) and even had dilikuidir ( bankrupt ) .The problems are formulated " Does PT . Tunas Prima Sejahterah Samarinda have used working capital efficiently . "The purpose of the study to determine the level of efficiency of the use of funds on PT.Tunas Prima Sejahterah Samarinda , while the usefulness of research as information for management to be able to manage the fund company well in the future .Basic theory used in Financial Management , Financial Reports , Working Capital , and Analysis of Sources and Uses of Working Capital . Based on the basic theory formulated hypotheses outlined as follows ; PT.Tunas Prima Sejahtera not use working capital efficiently .The analysis tool is used to compare the financial statements of the last two periods , whereas hypothesis testing criteria when running efficient use of working capital , the hypothesis is rejected and if the use of working capital is not running efficiently , the hypothesis diterima.Dari source analytical results obtained for working capitalRp 1,701,276,047.52 from the operating company that is profit , depreciation , fixed assets , capital stock , and a loan from the Bank . While the use of working capital of Rp 922,802,024.52 consisting of the addition of goods - goods inventory of Rp . 5,834,040.00 , bought the building Rp.403.916.020 , 52 , bought the vehicle is Rp . 513,051,964.00 cause an increase in working capital of Rp 778,474,023.00 participate in the purchase of fixed assets used tersebut.Hasil research at PT . Tunas Prima Sejahtera Samarinda short-term working capital loans used to finance long- term investments . Seen from the point of purchase / fund management appears that working capital is owned by the company has not utilized efficiently , it is seen that most of the accumulated working capital in the form of accounts receivable , and the use of many finance the purchase of fixed assets ., Thus the hypothesis alleged that PT . Tunas Prima Sejahterah not efficient in the use of funds held proven and accepted .